Systemic thrombolysis in acute ischemic stroke patients with unruptured intracranial aneurysms. (27th October 2015) - Goyal, Nitin; Tsivgoulis, Georgios; Zand, Ramin; Sharma, Vijay K.; Barlinn, Kristian; Male, Shailesh; Katsanos, Aristeidis H.; Bodechtel, Ulf; Iftikhar, Sulaiman; Arthur, Adam; Elijovich, Lucas; Alexandrov, Anne W.; et al.
Abstract : Objective: We sought to determine the safety of IV thrombolysis (IVT) in acute ischemic stroke (AIS) patients harboring unruptured intracranial aneurysm (UIA) in a multicenter study and a comprehensive meta-analysis of available case series. Methods: We analyzed prospectively collected data from consecutive AIS patients treated with IVT during a 4-year period at 4 tertiary-care stroke centers. All patients routinely underwent CT or magnetic resonance angiography during hospitalization. The presence of UIA was documented on the basis of neuroradiology reports. Symptomatic intracranial hemorrhage (sICH) was defined as imaging evidence of ICH combined with an increase in NIH Stroke Scale score of ≥4 points. A systematic meta-analysis of case series reporting safety of IVT in AIS with concomitant UIA was conducted according to PRISMA recommendations. Results: Among 1, 398 AIS patients treated with IVT, we identified 42 cases (3.0%) harboring a total of 48 UIAs. The rates of symptomatic and asymptomatic ICH were 2.4% (95% confidence interval [CI] by adjusted Wald method: 0%–12.6%) and 7.1% (95% CI: 1.8%–19.7%), respectively. A total of 5 case series met our inclusion criteria for meta-analysis, and the pooled rate of sICH among 120 IVT-treated AIS patients harboring UIA was 6.7% (95% CI: 3.1%–13.7%). In the overall analysis of 5 case-series studies, the risk ratio of sICH did not differ between AIS patients with and without UIA (risk ratio = 1.60; 95% CI: 0.54–4.77; p = 0.40) with no evidence of heterogeneity across included studies ( I 2 = 22% and p = 0.27 for Cochran Q test). Conclusions: Our prospectively collected multicenter data, coupled with the findings of the meta-analysis, indicate the potential safety of IVT in AIS patients with UIA.